2021
DOI: 10.1186/s42523-021-00080-w
|View full text |Cite
|
Sign up to set email alerts
|

The skin microbiome of Xenopus laevis and the effects of husbandry conditions

Abstract: Background Historically the main source of laboratory Xenopus laevis was the environment. The increase in genetically altered animals and evolving governmental constraints around using wild-caught animals for research has led to the establishment of resource centres that supply animals and reagents worldwide, such as the European Xenopus Resource Centre. In the last decade, centres were encouraged to keep animals in a “low microbial load” or “clean” state, where embryos are surface sterilized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 73 publications
(117 reference statements)
4
15
2
Order By: Relevance
“…However, it is unclear from 16S rRNA data whether this isolate is identical to the Chryseobacterium detected on tadpoles. None of the six genera of note identified here, with the exception of Pseudomonas , was found among the top 50 genera detected on tadpoles or adults in the recent Piccini et al study (Piccinni et al 2021), which is to date the only other such report of skin microbiota in Xenopus tadpoles. Although the data suggested that tadpole skin microbiomes are shaped environmentally, a lack of parental contribution was not directly determined.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…However, it is unclear from 16S rRNA data whether this isolate is identical to the Chryseobacterium detected on tadpoles. None of the six genera of note identified here, with the exception of Pseudomonas , was found among the top 50 genera detected on tadpoles or adults in the recent Piccini et al study (Piccinni et al 2021), which is to date the only other such report of skin microbiota in Xenopus tadpoles. Although the data suggested that tadpole skin microbiomes are shaped environmentally, a lack of parental contribution was not directly determined.…”
Section: Discussioncontrasting
confidence: 47%
“…However, this is almost certainly affected by differences in stage/age and sample collection methods. Piccini et al swabbed month old tadpoles (expected stage 54-55, length 60-80 mm) that had been fed algae and were housed in aquaria(Piccinni et al 2021), whereas those in our study were maintained in petri dishes in MMR at a constant 18 °C, were approximately 6-7 days old (stage 46, 9-12 mm length) at sampling, and had never been fed. Further, Piccini’s tadpoles and frogs were routinely raised for the first week in penicillin and streptomycin, and could therefore have acquired their microbiome from tank water and food(Piccinni et al 2021).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…While Xenopus microbiome work is in its infancy, Piccini et al 42 found that although the adult X. laevis skin microbiome is subject to strong selective pressures from the host, tadpole microbiomes were more variable and influenced by environmental conditions. Interestingly, the microbiomes of the older, premetamorphic tadpoles in the Piccini study 42 were also dominated by proteobacteria, although were not dominated by single genera as ours were. However, this is almost 54-55, length 60-80 mm) that had been fed algae and were housed in aquaria, 42 whereas those in our study were maintained in Petri dishes in MMR at a constant 18 C, were approximately 6-7 days old (stage 46, 9-12 mm length) at sampling and had never been fed.…”
mentioning
confidence: 99%